2003
DOI: 10.1034/j.1600-0625.12.s2.7.x
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of glycolic acid and lactic acid on melanin synthesis in melanoma cells

Abstract: Alpha-hydroxy acids (AHAs) such as glycolic acid (GA) and lactic acid (LA) have been reported to be effective in treating pigmentary lesions such as melasma, solar lentigines, and postinflammatory hyperpigmentation. The mechanism of this effect might be due to epidermal remodeling and accelerated desquamation, which would result in quick pigment dispersion. However, the direct effect of AHAs on melanin synthesis has not yet been well studied. To elucidate such a direct effect of AHAs on melanogenesis, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 51 publications
3
97
0
4
Order By: Relevance
“…Lactic acid is an alpha hydroxy acid (AHA) which facilitates desquamation of epidermal cells, melanin dispersion, and induces collagen and glycosaminoglycan deposition. Moreover, it has been reported to inhibit tyrosinase enzyme; therefore it was used in the treatment of melasma [20] . It induces the skin-lightening effect through three mechanisms, namely the induction of keratinocytes desquamation and the removal of melanosomes; the inhibition of tyrosinase; and the thickening of the epidermis and the dermis, so that the vasculatures become less visible [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid is an alpha hydroxy acid (AHA) which facilitates desquamation of epidermal cells, melanin dispersion, and induces collagen and glycosaminoglycan deposition. Moreover, it has been reported to inhibit tyrosinase enzyme; therefore it was used in the treatment of melasma [20] . It induces the skin-lightening effect through three mechanisms, namely the induction of keratinocytes desquamation and the removal of melanosomes; the inhibition of tyrosinase; and the thickening of the epidermis and the dermis, so that the vasculatures become less visible [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase activity was inhibited. No effect on tyrosinase, TRP-1 and TRP-2 mRNA [98] Study on topical application of a 10% glycolic acid for melasma showed improvement in 91% of patients [138].…”
Section: A-hydroxyacidmentioning
confidence: 99%
“…Except for their activity on acceleration of epidermal turnover [59,60,65,[95][96][97], several of these acids have also been shown to have effect on tyrosinase. For example, a-hydroxyacids is complementing its action on desquamation with direct inhibition of tyrosinase without influencing mRNA or protein expression [65,97,98]. The smallest a-hydroxy acid is glycolic acid (hydroxyacetic acid or 2-hydroxyethanoic acid).…”
Section: Acceleration Of Epidermal Turnover and Desquamationmentioning
confidence: 99%
“…35 Work by Sachdeva 36 has shown that lactic acid may be used for the treatment of acne scarring with minimal risk of any adverse events. In addition, Sharquie et al…”
Section: Lactic Acidmentioning
confidence: 99%